History Writes History - Karosas, Justinas (Problemos, 1986)
Cognitions of historical process are based upon correlations between factual (historiographical) and theoretical (sociological) aspects of the process. The theoretical aspect of historical knowledge provides historical facts with content. It is always linked to particular social stand and to this extent is subjective. The materialistic sociological methodology treats historical subjectivity as an expression of historical objectivity, and thus points out the basis for the explication of the problem of historical knowledge. By the end, it is the character of man’s material practice that determines the boundaries both of historical knowledge and of the realisation of its results.